(3bUjOI dGHf GdebaYs - (3YHO Gddg Hf GdebaY , GHf GdebaY , CHh YeQ,J (B142 (3g` s
(3ChdgG (B:s
(3hEPG hTgQ jYQa GdUja ebHdkG hPdc TgQ ai GdCfGe eMHH hajg MjGI ddHfGJ hQHeG CHGQ bGbfi hGdeHjQ eYjH s
(3BNQgG (B:s
(3hjbUO ajg GdYQa ef cGf YGdekG McjekG hjSJeQi GdCOjH GdegPH JeJ HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B156s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(57) s
(3JHUQI GdJQGLe(Bs
Keywords: (3GdeLGejYs